Urea Core Coating with Crosslinked Hydrophilic Polymers for Controlled Release Fertilizer Application - Sujono Sujono; Zainal A. Masud (Helium: Journal of Science and Applied Chemistry, 2021)
Controlled release fertilizer (CRF) can be made by coating the fertilizer core with a polymer layer. The simultaneous coating reaction of the polymerization needs to be controlled in the reactor. A controlled reactor system was developed for the polymerization of granular fertilizer coating using integrated electronic control of the 8-bit ATTiny 2313 AVR microcontroller chip. Urea granule fertilizer is coated with hydrophilic polymer polyacrylamide and crosslinked polyacrylate with N,N'-methylene-bis acrylamide (MBA). The reaction was initiated by benzoyl peroxide (BPO) at 61 oC. The coating was successfully formed in 45 minutes reaction. The coating process in the control reactor was more effective than without control, thereby reducing the deposition of polymer deposits that did not coat the fertilizer. The characterization of the fertilizer coating layer based on infrared spectroscopy (FTIR) showed that polymerization synthesis had occurred based on the presence of C=C bonds. The IR spectrum showed a reduced absorption of the C=C stretching vibration medium in the acrylamide monomer compared with the polymer (crosslinked polyacrylamide), namely the wavenumbers of 1614 cm-1 in acrylamide and 1601 cm-1 in polyacrylamide spectrum. Similarly, the loss of C=C absorption in the crosslinked polyacrylate spectrum but appeared in the acrylic monomer spectrum at 1636 cm-1 wave. This group is reduced or lost after polymerization due to an addition reaction.